Evaluation of Flexible Road Pavement Construction State Using Objective Strength Criteria - Saulius Butkevicius; Kazys Petkevicius; Kazys Petkevicius; Ipolitas Zenonas Kamaitis (The Baltic Journal of Road and Bridge Engineering)
This article illustrates that by means of our methodology for evaluation of state of flexible road pavement construction (RPC) it is possible with an adequate precision for practical purposes to measure the remaining resource of pavement construction strength and to suggest in every particular case the necessary measures to stop early and speedy deterioration of road pavement. For the application of the methodology mentioned above the following objective criteria have been established seeking to determine the state of pavement and its construction: RPC strength coefficient as well as remaining resource of this strength, resistance of asphalt concrete pavement or other asphalt material to binding tension, obligatory values of fatigue resistance coefficient of those materials and allowed value of RPC deterioration extent.